New Iterative Method Based on Laplace Decomposition Algorithm - Sabir Widatalla; M. Z. Liu (Journal of Applied Mathematics)
We introduce a new form of Laplace decomposition algorithm (LDA). By this form a new iterative method was achieved in which there is no need to calculate Adomian polynomials, which require so much computational time for higher-order approximations. We have implemented this method for the solutions of different types of nonlinear pantograph equations to support the proposed analysis.